Turmeric (Curcuma longa): an insight into its food applications, phytochemistry and pharmacological properties - Jikah, Agatha Ngukuran; Edo, Great Iruoghene (Vegetos - International journal of plant research, 2025)
Many people simply recognise turmeric; the golden-coloured powder as a spice, experimental and clinical research, has however, shown that the remedies of various diseases are also attributable to it, especially to its most potent bioactive curcuminoid, curcumin. Curcumin possesses antioxidant, antidiabetic, anti-inflammatory, antimicrobial, anticoagulant, cardiovascular, and central nervous system effects, but its utilization was before now limited due to its poor bioavailability and easy elimination. The development of adjuvants like piperine and other nano-formulations currently helps to overcome this limitation, and curcumin, now less limited, finds applications in diverse fields, including the medical, cosmetic, food, and agricultural industries. Other curcuminods, such as bisdemethoxycurcumin and demethoxycurcumin, are also present within the plant. This review aims to provide a look into the entire plant, beginning with its cultivation, processing, diseases, botanical details, bioactive compounds and their consequent activities, benefits from its bacterial fermentation, clinical applications on human subjects, as well as its utilization in the food, cosmetic, medical, and agricultural industries.